ANALISIS KARAKTERISTIK ECO-ENZYME DARI BUAH TROPIS - Nurdin Nurdin; Ai Nurlaila; Nina Herlina; Haydar Rahardian (Fakultas Kehutanan dan Lingkungan Universitas Kuningan, 2022)
The increase in population is in line with the increase in the volume of waste every day. Garbage in the form of skins or seeds is classified as organic waste originating from pineapple (Ananas comosus), oranges (Citrus reticulata), bananas (Musa paradisiaca L. var sapientum) and watermelon (Citrullus lanatus) which are often found in the environment around settlements without any processing. One alternative for processing organic waste is to process it into a multipurpose solution called eco-enzyme. Eco-enzymes utilize fruit or vegetable waste as organic raw materials. Organic matter is mixed with sugar and water in a ratio of 10 parts water, 3 parts organic matter and 1 part brown sugar and then fermented for 90 days. The result is a concentrated acid eco-enzyme solution with a pH value of 3.2 and a TDS value of 2393.8. The percentage reduction of eco-enzyme products during the fermentation process ranges from 2-33% depending on the maturity level of the raw materialsPeningkatan populasi jumlah penduduk seiring dengan naiknya volume sampah setiap hari. Sampah berupa kulit atau biji tergolong sampah organik yang berasal dari buah nanas (Ananas comosus), jeruk (Citrus reticulata), pisang (Musa paradisiaca L. var sapientum) dan semangka (Citrullus lanatus) banyak ditemukan di lingkungan sekitar pemukiman tanpa adanya pengolahan. Salah satu alternatif pengolahan sampah organik yaitu dengan diproses menjadi larutan multiguna yang disebut eco-enzyme. Eco-enzyme memanfaatkan sampah buah-buahan atau sayuran sebagai bahan baku organik. Bahan organik dicampur dengan gula dan air dengan perbandingan10 bagian air, 3 bagian bahan organik dan 1 bagian gula merah lalu difermentasi selama 90 hari. Hasilnya berupa larutan eco-enzyme asam pekat dengan nilai pH 3,2 dan nilai TDS 2393,8. Prosentase pengurangan produk eco-enzyme pada saat proses fermentasi berkisar antara 2-33% tergantung pada tingkat kematangan bahan baku